Neotype designation for Rodolia iceryae Janson in Ormerod, 1887 (Coleoptera: Coccinellidae) - Hounkpati, Kwevitoukoui; Forrester, Juanita A.; Mchugh, Joseph V. (Zootaxa, 2019)
The primary type of Rodolia iceryae Janson in Ormerod, 1887, a species commonly found in the Afrotropical region, is lost. In an effort to stabilize the specific epithet and to fix the taxonomic status and type locality of this economically important species, a neotype is here designated. A species diagnosis, illustrations of the male terminalia, and photographs of the neotype specimen and labels are provided.